Strengthening Lumansari Students: Promoting Awareness to Prevent and Address Bullying Effect - Sarah Latifah Ummah; Ahmad Ukasyah S; Masyhudan Ahmad; Alfunarrusda; Osa Marsanda Putri; Devi Marita Putri; Intan Rahma Sandhika; Mokhamad Iklil Mustofa (PROSIDING SEMINAR NASIONAL PENDIDIKAN, BAHASA, SASTRA, SENI, DAN BUDAYA, 2024)
Bullying among students is a serious issue that negatively affects the psychological and social development of students. Therefore, efforts are needed to raise students’ awareness of the impact of bullying and the importance of character education in preventing it. This community service activity aims to increase the awareness of students in Lumansari Village, Gemuh Subdistrict, Kendal Regency, regarding the impact of bullying through a character education approach. The methods used in this activity include socialization, group discussions, and positive character development training. The results of the activity showed a significant increase in students’ understanding of the negative impacts of bullying and the importance of values such as empathy, tolerance, and responsibility. It is hoped that this program can become a model that can be applied in other schools to prevent bullying and shape a generation with good character